Institutional change and political continuity in Post-Soviet Central Asia : power, perceptions, and pacts - Jones Luong, Pauline (Cambridge studies in comparative politics., 2002)
The establishment of electoral systems in Kazakhstan, Kyrgyzstan, and Uzbekistan presents both a complex set of empirical puzzles and a theoretical challenge. Why did three states with similar cultural, historical, and structural legacies establish such different electoral systems? How did these distinct outcomes result from strikingly similar institutional design processes?